2002
DOI: 10.2337/diabetes.51.7.2207
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Is a Predictor of Insulin Resistance in Human Pregnancy

Abstract: Historically, insulin resistance during pregnancy has been ascribed to increased production of placental hormones and cortisol. The purpose of this study was to test this hypothesis by correlating the longitudinal changes in insulin sensitivity during pregnancy with changes in placental hormones, cortisol, leptin, and tumor necrosis factor (TNF)-␣. Insulin resistance was assessed in 15 women (5 with gestational diabetes mellitus [GDM] and 10 with normal glucose tolerance) using the euglycemic-hyperinsulinemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
505
6
26

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 665 publications
(570 citation statements)
references
References 46 publications
33
505
6
26
Order By: Relevance
“…Furthermore, recent studies found that the rise in TNF-a and leptin levels during pregnancy are correlated with the decline in insulin sensitivity. 5 These data are in accordance with levels of leptin reported in the present study. Adiponectin is a novel adipocytokine produced abundantly and exclusively in adipose tissue.…”
Section: Commentsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, recent studies found that the rise in TNF-a and leptin levels during pregnancy are correlated with the decline in insulin sensitivity. 5 These data are in accordance with levels of leptin reported in the present study. Adiponectin is a novel adipocytokine produced abundantly and exclusively in adipose tissue.…”
Section: Commentsupporting
confidence: 93%
“…4 Lately, studies have implicated that adipocytokines, such as tumor necrosis factor alpha (TNF)-a) and leptin, are probable regulators of insulin resistance in pregnancy. 5 Adiponectin is an adipocytokine produced abundantly and exclusively in adipose tissue. A large body of evidence from experimental and epidemiological studies in adults has supported the important role of adiponectin in regulating insulin resistance and glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, this could also be contributed to by the low-grade inflammatory situation originating in white adipose tissue and placenta through increased production of various cytokines including IL-6 and TNF-α [46,47]. In addition, TNF-α is the best predictor of peripheral insulin resistance during pregnancy and, at the same time, is able to reduce adiponectin expression and secretion [45,48]. Taking all of this into account, we view the pregnancy-mediated increase in TNF-α as an important functional link between hypoadiponectinaemia and insulin resistance.…”
Section: Functional Significance Of Hypoadiponectinaemiamentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM), a state of increased insulin resistance, can lead to complications during pregnancy and may also increase the risk of stillbirth [8].…”
Section: Introductionmentioning
confidence: 99%